(untitled) (Comprehensive Journal of Science, 2026)
Abstract: This study aimed to delve deeper into the impact of good governance on improving the performance of Libyan commercial banks through several indicators that reflect this relationship, the most important of which are disclosure and transparency indicators and the tasks and responsibilities of the banks’ boards of directors. To this end, questionnaires were distributed using a comprehensive survey method to all administrative employees at the Al-Jumhouria Bank, Al-Khums branch. The study reached a number of results, the most important of which is the existence of a statistically significant impact between the application of the principles of good banking governance on improving the financial performance of the Al-Jumhouria Bank, Al-Khums branch. Also, the dimension of disclosure and transparency has a strong impact on the bank’s financial performance. Therefore, good governance has an effective impact on improving the financial performance of commercial banks.